2020
DOI: 10.1109/access.2020.3008211
|View full text |Cite
|
Sign up to set email alerts
|

Complex Fault Source Identification Method for High-Voltage Trip-Offs of Wind Farms Based on SU-MRMR and PSO-SVM

Abstract: Large-scale high-voltage trip-offs (HVTOs) of wind farms are serious incidents afflicting power systems that can lead to voltage instability, power deficiency, and frequency fluctuation. In order to reduce the influence of HVTOs, it is necessary to efficiently identify the fault source after an HVTO at a wind farm. A fault source identification method for wind farm HVTOs is proposed in this work. First, the fault tree analysis (FTA) method is used to summarize the causal and logical relationships among the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Authors in [40] suggested a hybrid fault diagnostic strategy that uses SVM and enhanced particle swarm optimization (PSO) to perform additional diagnostics based on qualitative reasoning. A technique for fault source detection and identification of wind farm high-voltage trip-offs is proposed in [41] based on multi-dimensional attribute indices and the PSO-SVM method. The PSO method is utilized in the hyperparameters SVM optimization for better classification performance in the unbalance and balance mode, single and/or compound fault source identification.…”
Section: A Related Workmentioning
confidence: 99%
“…Authors in [40] suggested a hybrid fault diagnostic strategy that uses SVM and enhanced particle swarm optimization (PSO) to perform additional diagnostics based on qualitative reasoning. A technique for fault source detection and identification of wind farm high-voltage trip-offs is proposed in [41] based on multi-dimensional attribute indices and the PSO-SVM method. The PSO method is utilized in the hyperparameters SVM optimization for better classification performance in the unbalance and balance mode, single and/or compound fault source identification.…”
Section: A Related Workmentioning
confidence: 99%
“…e algorithm was effective in high-precision wind speed predictions. Reference [12] proposed a particle swarm optimization-based support vector machine for power forecasting, but there were problems with excessive errors.…”
Section: Introductionmentioning
confidence: 99%